In vivo Analgesic, Anti-hyperglycaemic and CNS Depressant Studies of Commelina paludosa Blume (Bangladesh Pharmaceutical Journal, 2020)
The methanol extract of whole plant of Commelina paludosa Blume (family: Commelinaceae) has been screened to explore its in vivo central and peripheral analgesic, hypoglycaemic and central nervous system depressant activities in Swiss Albino mice. The crude extract significantly increased the latent response time in tail-flick method (p